Dampak Penggantian Jagung Giling dengan Tepung Kulit Pisang Hasil Fermentasi dalam Pakan Konsentrat dan Imbuhan Zn Biokompleks terhadap Profil Darah Sapi Bali Jantan Penggemukan - Nenat, Maria Febiola; Amalo, Daud; Kihe, Johny Nada; Sobang, Yohanis Umbu Laiya (Yayasan Sumber Daya Manusia Cerdas, 2025)
This study aimed to analyze the impact of replacing milled corn with fermented banana peel flour (KPF) and Zn-biocomplex supplemented concentrate feed on the blood profile of fattening male Bali cattle. Twelve male Bali cattle aged 2–2.5 years, with a body weight range of 130.5–175.5 kg (coefficient of variation: 7.87%), were used in a completely randomized experimental design. The treatments were as follows: P0 (70% forage + 30% concentrate without KPF substitution), P1 (25% KPF substitution), P2 (50% KPF substitution), and P3 (75% KPF substitution). Results showed erythrocyte levels (10⁶/µl) of P0: 10.06 ± 0.48; P1: 10.37 ± 0.45; P2: 11.06 ± 0.06; P3: 10.26 ± 0.17. Leukocyte levels (10⁴/µl) were P0: 10.68 ± 0.61; P1: 11.56 ± 0.46; P2: 11.14 ± 1.08; P3: 10.75 ± 0.72. Hematocrit levels (%) were P0: 31 ± 2.40; P1: 33.36 ± 1.11; P2: 33.79 ± 1.32; P3: 32.26 ± 1.16. Analysis of variance (ANOVA) indicated no significant differences (P > 0.05) in erythrocyte, leukocyte, or hematocrit levels among treatments. In conclusion, substituting up to 75% of milled corn with KPF in the concentrate feed, combined with Zn-biocomplex supplementation, did not adversely affect the blood profile of fattening male Bali cattle. This suggests that fermented banana peel flour can serve as a viable alternative to corn in cattle feed formulations.